Dupuytren’s Contracture in Athletes - Tomasz Antczak; Monika Gajda-Bathelt; Monika Dąbek; Katarzyna Jania; Zuzanna Perlicka; Karolina Smolińska; Paulina Sadkowska; Julia Kulczycka; Weronika Popow; Michał Ciołkosz (Quality in Sport)
Background. Dupuytren’s contracture is a fibrotic condition of the hand, traditionally associated with age, genetics, and metabolic factors. However, recent observations suggest it may also appear in younger individuals with high physical activity levels.